Phase 1 Study to Evaluate the Effect of the Investigational Anticancer Agent Sapanisertib on the QTc Interval in Patients With Advanced Solid Tumors. Issue 7 (2nd June 2020) - Patel, Chirag; Goel, Sanjay; Patel, Manish R.; Rangachari, Lakshmi; Wilbur, Jayson D.; Shou, Yaping; Venkatakrishnan, Karthik; Lockhart, A. Craig
Abstract: The aim of this phase 1 study was to determine the effects of sapanisertib on the heart rate–corrected QT (QTc) interval in patients with advanced solid tumors. Adult patients with advanced solid tumors were enrolled to receive a single sapanisertib 40‐mg dose. Blood samples for pharmacokinetic analysis were collected and electrocardiogram readings were recorded at baseline and up to 48 hours after dosing. Patients could continue to receive sapanisertib 30 mg once weekly in 28‐day cycles for up to 12 months. The primary objective was to characterize the effect of a single dose of sapanisertib (40 mg) on the QT interval. Secondary objectives were to evaluate safety, tolerability, and pharmacokinetics. Following a single sapanisertib 40‐mg dose in 44 patients, the maximum least squares mean (upper bound of 1‐sided 95% confidence interval) changes from time‐matched baseline were 7.1 milliseconds (11.4 milliseconds) for individual rate‐corrected QT interval at 24 hours after dosing, and 1.8 milliseconds (5.6 milliseconds) for Fridericia‐corrected QTc at 1 hour post‐dose. There was no sapanisertib plasma concentration‐dependent increase in the change from time‐matched baseline individual rate‐corrected QTc interval or Fridericia‐corrected QTc. The most common adverse events following sapanisertib 30 mg once‐weekly dosing were nausea (80%), fatigue (61%), vomiting (57%), and decreased appetite (45%). A single sapanisertib 40 mg dose did not produce clinically relevant effects on QTc interval in patients with advanced solid tumors. The safety profile of sapanisertib 30 mg once weekly was favorable, and no new safety signals were observed (NCT02197572, clinicaltrials.gov).